A look to investigations on research formation at Latin American universities: state of the art 2010 to 2017 - Lopéz- de Parra, Lillyam; Polanco-Perdomo, Viviana; Correa-Cruz, Lucelly (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The purpose of this article is to identify the research characteristics developed in the universities of Latin America about the research development between 2010 and 2017. The methodology used was qualitative, documentary and descriptive. The unit analysis was composed by 56 researches published in Spanish and consulted in some databases. They were selected and systematized in the following categories: countries, aims, topics, methodology approaches and techniques, results, the new, the absent and the difficulties. The results highlight several topics of formative research: formation, productivity, social representations, perceptions and attitudes, competences and skills. Countries with high production: Colombia, Mexico, Cuba, Chile, Peru and Venezuela. The methodology used is varied: qualitative, quantitative, mixed or qualitative-quantitative. The advances are given by the explanatory researches that contribute to the formation of theory. In addition, the importance of the relationship between formative research and the improvement and qualification of vocational formation is highlighted. The recommendation for research training emerges from the formulation and development of relevant projects that impact on the community and promote research, the raison d'être of universities.